Acceptability of two colorectal cancer screening tests: pain as a key determinant in sigmoidoscopy - Kirkøen, Benedicte; Berstad, Paula; Botteri, Edoardo; Dalén, Eirin; Nilsen, Jens Aksel; Hoff, Geir; de Lange, Thomas; Bernklev, Tomm (Endoscopy, 2017)
Background Participants’ experience with a screening test can influence adherence, and therefore the efficacy of screening programs. We compared screening with unsedated flexible sigmoidoscopy and fecal immunochemical testing (FIT) for participants’ satisfaction with the decision and for willingness to repeat colorectal cancer screening. Methods In a prospective, randomized trial 3257 individuals (50 – 74 years) were invited to either flexible sigmoidoscopy or FIT (1:1), of whom 1650 took up the offer (52.6 %). In total, 1497 screening participants completed at least one questionnaire, either before screening, and/or at three time points in the following year, that measured willingness to repeat screening, willingness to recommend screening, and satisfaction with decision to attend. There were 769 and 728 responders in the flexible sigmoidoscopy and FIT group, respectively. Additionally, 581 flexible sigmoidoscopy participants also completed a pain questionnaire. Results 1 year later, 10 % of the flexible sigmoidoscopy participants were not willing to repeat screening, compared to 5 % of FIT participants. A higher percentage of women compared to men would not repeat flexible sigmoidoscopy screening (adjusted odds ratio [OR] 2.52, 95 % confidence interval [95 %CI] 1.48 to 4.28). Notably, 22 % of women reported pain during flexible sigmoidoscopy compared to 5 % of men. When we added pain to the statistical model, pain was significantly associated with unwillingness to repeat flexible sigmoidoscopy (OR 3.15, 95 %CI 1.68 to 5.87), while gender was no longer associated (OR 1.53, 95 %CI 0.82 to 2.88).Conclusion Acceptability for flexible sigmoidoscopy and for FIT was high among Norwegian screening participants, though FIT participants were more willing to repeat screening. Women were less willing to repeat screening with flexible sigmoidoscopy compared to men. This gender difference seemed partly due to pain, and therefore preventable.This study is registered at ClinicalTrials.gov: NCT01538550.